Справочник цехового (промыслового) энергетика: учеб.-практ. пособие / Л. Е. Старкова - Старкова Л. Е. (Инфра-Инженерия, 2009)
Экземпляры: ТО (20110215) / Инвентарный номер: 1082610 / Цена: / Сис.шифр: 31.29 / Авт.знак: С 77 / ГРНТИ: 45 / ББК: 31.29-5